SAT0230 New oral anicoagulants in patients with antiphospholipid syndrome. (15th June 2017) - Satybaldyeva, MA; Seredavkina, N; Kashnikova, L; Nasonov, E; Reshetnyak, T
Abstract : Background: Antiphospholipid syndrome (APS) is an acquired thrombophilia characterized by reccurent venous and arterial thrombosis, obstetric pathology (fetal loss), and synthesis of antiphospholipid antibodies. Warfarin is a "golden" standard of APS therapy. However it has number of disadvantages. Dabigatran etexilate is a direct thrombin inhibitor and its main differences from warfarin are fixed dose, no need of regular INR monitoring, less elimination half-life. Objectives: To evaluate efficacy and safety of dabigatran etexilate in patients with APS. Methods: 38 patients (pts) (F:26, M:12) with primary and secondary APS, 37, 2±9, 9 years old. 24 pts with primary APS, 14 pts with secondary APS: 13 had systemic lupus erythematosus (SLE) + APS, 1 rheumathoid arthritis (RA) + APS. The diagnosis of APS was established due to international APS criteria (Sydney), SLE – SLICC 2012, RA - ACR/EULAR 2010. The majority number of pts (n=28) received warfarin, others – sulodexide (n=1), low molecular heparin (n=1), had no anticoagulant therapy (n=3), 5 pts received dabigatran etexilate before inclusion to trial. The control of coagulogram was done 3 times: before inclusion to trial, in 24 weeks and in 48 weeks after inclusion. Trial assays were performed in the laboratory in V.A. Nasonova Research Institute of Rheumatology, Moscow, Russian Federation. APPT and thrombin time tests were done with the automated coagulometer Coalysys Plus C (Behnk Electronic, Germany); thrombin time test was done with STA-thrombin reagent (Diagnostica Stago, France), APPT with STA-Cephascreen reagent (Diagnostica Stago, France). Lupus anticoagulant was assessed by the dilute Russell's viper venom time, using Siemens Healthcare (Germany) LA1 (screening) and LA2 (confirmation). IgG or IgM antibodies against cardiolipin and β2 glycoprotein I (β2GPI) were measured with automated enzyme-immunoassay analyzer Alegria with Anti-Cardiolipin IgG/IgM and Anti-beta-2-Glycoprotein I IgG/IgM reagents (Orgentec Diagnostika GmbH, Germany). Triple positivity was defined as positive antibodies against cardiolipin and β2GPI and a positive test for lupus anticoagulant. Results: 32 pts had high or medium level of aPL (anticardiolipin antibodies IgG, IgM, anti-β2glycoprotein antibodies IgG, IgM), 6 had low or normal level of aPL. 12 pts were triple positive. APPT and thrombin time before inclusion to trial were 44, 2 [36, 5;53, 5] and 16, 1 [14, 9;17, 0], on 24 week after dabigatran etexilate start 51, 0 [40, 5;65, 7] and 163, 5 [108, 7;240, 0] and on 48 week 58, 7 [45, 6;63, 2] and 194, 1 [152, 6;255, 2] respectively.1 patient was excluded due to non-compliance. During follow-up period from 1, 5 to 12 (10, 6±3, 2) months 7 pts (22, 6%, 20, 7 per 100 patient-years) experienced reccurent thrombosis including superficial vein thrombosis (n=2; 6, 5%, 5, 9 per 100 patient-years), thrombosis of paranephric veins (n=1; 3, 2%, 2, 9 per 100 patient-years), acute cerebrovascular disorders (n=4; 12, 9%, 11, 8 per 100 patient-years). All pts with reccurent thrombosis had high or medium level of aPL; 2/7 were triple positive, both had acute cerebrovascular disorders. 5 pts (16, 1%, 14, 8 per 100 patient-years) experienced bleeding: 2 hemorrhoidal bleedings, 1 uterine bleeding, 2 nasal bleedings. There was no case of severe bleeding. Conclusions: Dabigatran etexilate could be used in patients with APS in the case of warfarin non-effectiveness. These findings need to be confirmed in larger studies. Disclosure of Interest: None declared